Adobe indesign cs6 - (3NejS, CMeO MSfs ((3GdGScfOQjIs (3GdeQcR GdeUQi dJHSjW GdYdhes, 2014)
(3HQfGeL jSJNOe ai JUeje UaMGJ GdcJH hUaMGJ GdeLdGJs
(3jMJhi ehShYI GdLQGajcS Ydi (B20(3GSWhGfI (Bdvd (3JMJhi Ydi TQM hGai dHQGeL GdLQGajcS GdeNJdaI HOGjI ef HQfGeL GdahJhThH GdTgjQ eQhQG HHQGeL GdjSJQGJhQ hGfOjRGjf hadGT hUhdG Gdi HQGeL HQjejjQ hGaJQGacJS hGhOjTf hGdeDKQGJ GdUhJjI hGdNWhW GdYQHjI hGdGfLdjRjI hcGaI GdGOhGJ hGdadGJQ hGddGReI dJchf HPdc bO GeJdcJ GdTQM GdNGU HHQGeL GdLQGajcS hGjVG GOhGJ GdJfajPs
3 7
Keywords: (3GdMGSHGJ GdGdjgs -- (3HQGeL QSe LQGajcis